The ripple tank as medium for exploring wave phenomena - Lopez, Lydia C. 1939- (s.n.], 1966)
The author presented the qualitative aspects of wave interactions in order to develop an increasing appreciation for waves not so much because of its applications but because of its own value and importance as one of the unifying physical concepts. The presentation of the wave phenomena through the use of a rippled tank is patterned after the PSSC approach.